Równania Teorii Dużych Ugięć Powłok Plastycznych - Duszek, M. (Engineering Transactions, 1972)
The paper is aimed at the determination of the equations of the theory of plastic, incompressible shells, account being taken of the geometry changes produced by plastic deformation. Using the Lagrangean description (referred to the initial configuration) a systematic classification of the stressstrain relations has been done, their form being specified in dependence of the shell geometry assumed and of the admissible values of the individual displacement vector components. The estimation of the generalized variables and the equilibrium equations are then discussed, as also the principles of formulation of the yield conditions in the theory of large deflections. Finally, the fundamental relations concerning certain particular cases of cylindrical and spherical shells are given.